A case report of neuronal intranuclear inclusion disease and literature review - Jie Li; Guogao Zhang; Jianrong Zheng; Jun Hu; Yunong Li (BMC Neurology)
Abstract Neuronal intranuclear inclusion disease (NIID) is a rare progressive neurodegenerative disease with a characteristic pathological feature of eosinophilic hyaluronan inclusions in the nervous system and internal organs. The identification of GGC-repeat expansions in the Notch 2 N-terminal like C (NOTCH2NLC) gene facilitates the accurate diagnosis of NIID. Due to its rareness and high clinical heterogeneity, the diagnosis of NIID is often delayed or missed. Here, we report a case of NIID mimicking autoimmune encephalitis. A 55-year-old Chinese man presented with fever, headache, recurrent seizures, and weakness in the upper and lower left limbs. Brain MRI revealed diffuse T2/ FLAIR-hyperintense lesions in the bilateral basal ganglia, corpus callosum, and periventricular white matter, with swelling of the right temporal, frontal, and parietal cortices accompanied by meningeal enhancement. Abnormally high signal lesions were observed in the corticomedullary junction in diffusion-weighted imaging (DWI). The infectious or autoimmune disease screening of central nervous system using CSF was normal. The test of GGC-repeat expansion in the NOTCH2NLC gene by capillary electrophoresis indicated GGC repeats (48 and 110 GGC repeats), which supported the diagnosis of NIID. After treatment with glucocorticoid, the clinical symptoms of this patient improved significantly. In the literature, 12 cases of NIID presenting with encephalitis-like attacks were identified, most of which were recurrent, accompanied by progressive symptoms such as dementia, Parkinsonism symptoms, migraine, or dysuria. In this case, there was a single encephalitis-like episode without other progressive symptoms. In patients with encephalitis-like symptoms, NIID should be considered, especially when no other evidence of infection is found, as demonstrated in this case. In addition, long-term monitoring of disease progression is also very important.